Association between indoor nitrous acid, outdoor nitrogen dioxide, and asthma attacks: results of a pilot study. Issue 6 (2nd November 2019) - Ohyama, Masayuki; Nakajima, Takae; Minejima, Chika; Azuma, Kenichi; Oka, Kenji; Itano, Yasuyuki; Kudo, Shouichiro; Takenaka, Norimichi
ABSTRACT: The association between nitrogen dioxide (NO2 ) and asthma has been investigated. However, conventional NO2 assays measure nitrous acid (HONO) as NO2 . In this pilot epidemiological observational study, we assessed exposure to indoor HONO and some air pollutants in pediatric asthma patients and examined possible association between exposure and asthma symptoms. Indoor HONO and nitric oxide (NO), which are primarily generated by the combustion of certain substances, were significantly associated with asthma attacks in 2010. In 2010, indoor HONO was closely correlated with indoor NO than with outdoor NO2 . Conversely, in 2012, indoor HONO was closely correlated with outdoor NO2 and NO than with indoor NO2 and NO. Outdoor NO2 was significantly associated with asthma attacks in 2012. Our results highlight the need for further epidemiological studies of the association between indoor HONO and asthma symptoms using multivariate analyses to examine the role of NO2 in asthma symptoms. Abbreviations : CXCL1: the chemokine (C-X-C motif) ligand 1; EP: the entire study period; FP: the first half of study period; HONO: nitrous acid; NO: nitric oxide; NO2 : nitrogen dioxide; OH radical: hydroxyl radical; SP: the second half of study period; TNF-α: tumor necrosis factor-α; US EPA: United States Environmental Protection Agency; WHO: World Health Organization.